Engineering Curcumin Biosynthesis in Poplar Affects Lignification and Biomass Yield - De Meester, Barbara; Oyarce, Paula; Vanholme, Ruben; Van Acker, Rebecca; Tsuji, Yukiko; Vangeel, Thijs; Van den Bosch, Sander; Van Doorsselaere, Jan; Sels, Bert; Ralph, John; Boerjan, Wout (Frontiers in Plant Science, 2022)
Lignocellulosic biomass is recalcitrant towards deconstruction into simple sugars mainly due to the presence of lignin. By engineering plants to partially replace traditional lignin monomers with alternative ones, lignin degradability and extractability can be enhanced. Previously, the alternative monomer curcumin has been successfully produced and incorporated into lignified cell walls of Arabidopsis by the heterologous expression of DIKETIDE-CoA SYNTHASE (DCS) and CURCUMIN SYNTHASE2 (CURS2). The resulting transgenic plants did not suffer from yield penalties and had an increased saccharification yield after alkaline pretreatment. Here, we translated this strategy into the bio-energy crop poplar. Via the heterologous expression of DCS and CURS2 under the control of the secondary cell wall CELLULOSE SYNTHASE A8-B promoter (ProCesA8-B), curcumin was also produced and incorporated into the lignified cell walls of poplar. ProCesA8-B:DCS_CURS2 transgenic poplars, however, suffered from shoot-tip necrosis and yield penalties. Compared to that of the wild-type (WT), the wood of transgenic poplars had 21% less cellulose, 28% more matrix polysaccharides, 23% more lignin and a significantly altered lignin composition. More specifically, ProCesA8-B:DCS_CURS2 lignin had a reduced syringyl/guaiacyl unit (S/G) ratio, an increased frequency of p-hydroxyphenyl (H) units, a decreased frequency of p-hydroxybenzoates and a higher fraction of phenylcoumaran units. Without, or with alkaline or hot water pretreatment, the saccharification efficiency of the transgenic lines was equal to that of the WT. These differences in (growth) phenotype illustrate that translational research in crops is essential to assess the value of an engineering strategy for applications. Further fine-tuning of this research strategy (e.g. by using more specific promoters or by translating this strategy to other crops such as maize) might lead to transgenic bio-energy crops with cell walls more amenable to deconstruction without settling in yield.